OFFSET
1,2
COMMENTS
Equivalently, numbers of the form 2^y(x+2)-y-2.
Using f(1,x,y) = f(0, f(1,x,y-1), f(1,x,y-1)+y) = 2*f(1,x,y-1) + y
f(1,x,y) + y + 2 = 2*(f(1,x,y-1)+y-1+2) let g(y) = f(1,x,y) + y + 2 then g(y) = 2*g(y-1). This means g(y)=2^y*g(0) and f(1,x,y) + y + 2 = 2^y(f(1,x,0)+2) but f(1,x,0) = x so f(1,x,y) = 2^y(x+2) - y - 2.
In this list we suppose that y>0. If we include y=0, every natural number would be in the sequence.
EXAMPLE
19 is listed because f(1,1,3) = 2^3*(1+2) - 3 - 2 = 19.
CROSSREFS
KEYWORD
nonn
AUTHOR
Natan Arie Consigli, Jul 23 2015
STATUS
approved